PERFORMATIVE DISCOURSE INERTIA OF «TESTAMENT» BY T. SHEVCHENKO - Луцак, С. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article T. Shevchenko’s «Testament» is considered as peculiar natiosophical «message in the act of writing», picked up and deployed by other authors (Ivan Franko, Lesya Ukrainka, Vasyl Stus), given the key intentions of the original text aimed at the efficient conversion of Ukrainian ethnicity into statelike nation.